Parenting style and empathy in children: The mediating role of family communication patterns - Sarrah Hasyim Abdullah; Rose Mini Agoes Salim (HUMANITAS: Indonesian Psychological Journal, 2020)
Behavior problems among children in Indonesia are still high. The number of children involved in legal problems shows that there are existing moral problems. A crucial component in morals is empathy. Family, as the primary system in a child's life, has a significant influence on the development of empathy in children. This research was conducted to analyze the effect of parenting style on empathy in children through family communication patterns in early childhood in Indonesia. As many as 233 parents of 6 - 8 years old children participated in this study. The Parental Authority Questionnaire-Revised (PAQ-R), Basic Empathy Scale - Parent Report (BES-PR) and Family Communication Patterns-Revised (FCP-R) were used to collect the data. The results of this study indicate that family communication patterns mediate the relationship between parenting style and empathy in children. Conversational communication pattern mediate the effect of both authoritative parenting and permissive parenting on child's empathy independently. Conformity communication pattern only mediate the influence of authoritarian parenting on empathy in children. The current findings add information about the understanding about parenting strategies and interactions as well as the role of the family in the development of empathy in children.